2012
DOI: 10.1016/j.intell.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Are g and the General Factor of Personality (GFP) correlated?

Abstract: Highlights:>We examined whether the General Factor of Personality is correlated with g. >The analysis used data from 4,462 Vietnam era veterans randomly sampled from five million soldiers. >Measures were the MMPI and 15 cognitive ability tests. >Two hierarchical confirmatory factor models were jointly estimated. >The correlation between the general factors at the apex was -0.23. , that is, the higher the g score the higher the score on the GFP. One possible reason for the low correlation is restriction of rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
(77 reference statements)
1
20
1
Order By: Relevance
“…Regarding this, we stated that knowing what to say and how to behave during an important interview is a complex social skill and there is no reason to assume that individuals who possess such skills will not use it during their everyday (working) life when dealing with others. In this sense, it may resemble Hogan's notion of ‘… getting along in order to get ahead’ (see Irwing et al, ), which may be one important component of the GFP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding this, we stated that knowing what to say and how to behave during an important interview is a complex social skill and there is no reason to assume that individuals who possess such skills will not use it during their everyday (working) life when dealing with others. In this sense, it may resemble Hogan's notion of ‘… getting along in order to get ahead’ (see Irwing et al, ), which may be one important component of the GFP.…”
Section: Discussionmentioning
confidence: 94%
“…. getting along in order to get ahead' (see Irwing et al, 2012), which may be one important component of the GFP.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Vietnam Experience study containing 4462 Vietnam War veterans, Irwing et al (2012) examined the relation between MMPI score and g. A significant negative correlation was found (because the MMPI assesses psychopathology) of -.23 between GFP (Abnormal) and g. The authors conclude that the reason for this low (yet significant correlation) is that both intelligence and personality are to a degree mutually exclusive evolutionary survival strategies, the first aimed at generating resources and the second at maximizing one's share of resources. Dunkel (2013) used Q-sort data from a longitudinal child development study to examine relation between the other-rated GFP and g. There were significant associations between the GFP and g scores across the study waves with the correlation between average g and GFP (across ages) being .46. , this time using data from a longitudinal study of high school students collected in the 1960s.…”
Section: Personality and Intelligencementioning
confidence: 99%
“…It was found that the general factor of personality was moderately related to the Overall Assessment Rating. It is also known that a higher general mental ability score is related to a higher score on the general factor of personality (Irwing, Booth, Nyborg, & Rushton, 2012). However, no studies have as yet examined the relations between metatraits and, for example, social and achievement strategies, even though the latter could be expected to be closely related to the general factor of personality as an indicator of good overall functioning.…”
Section: Psychological Assessment Of Applicants To Ministrymentioning
confidence: 99%